2017
DOI: 10.1142/s0219525917500072
|View full text |Cite
|
Sign up to set email alerts
|

Market Fluctuations Explained by Dividends and Investor Networks

Abstract: The inability of investors and academics to consistently predict, and understand the behavior of¯nancial markets has forced the search for alternative analytical frameworks. Analyzinḡ nancial markets as complex systems is a framework that has demonstrated great promises, with the use of agent-based models (ABMs) and the inclusion of network science playing an important role in increasing the relevance of the framework. Using an arti¯cial stock market created via an ABM, this paper provides a signi¯cant insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Table 3 provides a summary of the baseline settings and parameter changes utilized for the various experiments. The settings were chosen to ensure a level of consistency against Harras & Sornette [37] and Oldham ( [23,27]). These papers reported that as the variable that determines the inclination of the investor to be influenced by their network increases-denoted by c 1 (see (1))-the price series begins to experience increased periods of volatility.…”
Section: Cutting Poor Advisers and Selecting New Advisers (Steps 10a-mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 provides a summary of the baseline settings and parameter changes utilized for the various experiments. The settings were chosen to ensure a level of consistency against Harras & Sornette [37] and Oldham ( [23,27]). These papers reported that as the variable that determines the inclination of the investor to be influenced by their network increases-denoted by c 1 (see (1))-the price series begins to experience increased periods of volatility.…”
Section: Cutting Poor Advisers and Selecting New Advisers (Steps 10a-mentioning
confidence: 99%
“…Allowing investors to interact with and receive information from other investors enables them to form an information network. The critical consequences of this process are that investor networks and financial networks in general have been found to be capable of affecting the behavior of the market ( [22][23][24]), and they explain trading volumes and the performance of investors ( [25,26]). Critically, this analysis has not been, nor can it be, considered in the models underwritten by a representative agent approach.…”
Section: Introductionmentioning
confidence: 99%